Politics and Green Financial Crime: Envisioning a Sustainable Democratic Future in Indonesia - Putra, Yagie Sagita; Pujiyono, Pujiyono; Rochaeti, Nur; Fernando, Zico Junius (Faculty of Law, Universitas Jenderal Soedirman, 2024)
This research investigates the link between environmental crimes and political corruption in Indonesia, focusing on findings by the Indonesian Financial Transaction Reports and Analysis Center (PPATK). PPATK reported that approximately 1 trillion Rupiah, derived from green financial crimes such as illegal logging and environmental exploitation, has been funneled into political campaigns ahead of the 2024 elections. These illicit financial flows threaten electoral integrity, environmental sustainability, and democratic governance. Utilizing a normative legal research method with legislative, conceptual, comparative, and futuristic approaches, this study identifies gaps in existing political funding regulations and oversight mechanisms. The findings reveal that the lack of transparency and accountability in campaign financing allows environmental criminals to influence policymaking, thereby weakening green policies and governance. To address this issue, the study proposes actionable solutions: strengthening independent oversight institutions, enforcing strict political financing transparency, adopting a risk-based approach to financial regulations, increasing public participation, and enhancing international cooperation. Collective action from civil society, policymakers, and global partners is imperative to safeguard Indonesia’s democratic values and environmental heritage.Keywords: Environmental Crimes; Green Financial Crime; Indonesia; Politics.